2021
DOI: 10.1016/j.virol.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human adenovirus replication inhibitors from a library of small molecules targeting cellular epigenetic regulators

Abstract: Human adenovirus (HAdV) can cause severe disease in certain at-risk populations such as newborns, the elderly and those with compromised immune systems. Unfortunately, no FDA-approved anti-HAdV drug is currently available for treatment. Within the nucleus of infected cells, the HAdV genome associates with histones and forms a chromatin-like structure during early infection, and viral gene expression appears regulated by cellular epigenetic processes. Thus, one potential therapeutic strategy to combat HAdV dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Another anti-HIV agent, stavudine (a thymidine analogue) was also found to be potent against HAdV [124]. Furthermore, we observed that gemcitabine, a cytidine analogue and a chemotherapeutic agent, abrogates gene expression and the replication of HAdV-4, HAdV-5 and HAdV-7 [126], while cytarabine led to modest effects on HAdV-5 gene expression and yield [127]. These compounds may prove to be useful in cases where cidofovir fails to improve disease outcome, but thorough assessment of their efficacy and safety in animal models is required prior to clinical testing.…”
Section: Compound Reference(s)mentioning
confidence: 79%
See 4 more Smart Citations
“…Another anti-HIV agent, stavudine (a thymidine analogue) was also found to be potent against HAdV [124]. Furthermore, we observed that gemcitabine, a cytidine analogue and a chemotherapeutic agent, abrogates gene expression and the replication of HAdV-4, HAdV-5 and HAdV-7 [126], while cytarabine led to modest effects on HAdV-5 gene expression and yield [127]. These compounds may prove to be useful in cases where cidofovir fails to improve disease outcome, but thorough assessment of their efficacy and safety in animal models is required prior to clinical testing.…”
Section: Compound Reference(s)mentioning
confidence: 79%
“…Nucleoside/nucleotide analogues Zalcitabine [118,122,123] Alvoudine [118] Stavudine [124] Acyclic nucleoside phosphonate analogues of cidofovir [118] Various ether lipid-ester prodrugs of cidofovir [125] Gemcitabine [126] Cytarabine [127] Other nucleoside/nucleotide analogues [128] Inhibitors of epigenetic regulators…”
Section: Compound Reference(s)mentioning
confidence: 99%
See 3 more Smart Citations